Pengaruh Media Tanam Dan Jenis Tanaman Pada Constructed Wetland Untuk Pengolahan Limbah Industri Tahu - Achmad, Arini Sayyidah; Amalia, Aussie (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Waste treatment is the main challenge in the tofu industry, especially for household-scale producers. As a solution, constructed wetland is an affordable, efficient, and easy-to-operate waste treatment method. The tofu industrial wastewater used in this study came from one of the home industries in the park, Sidoarjo. In this study, a variety of planting media and plant types were used. The planting media used are silica sand and gravel; biochar and mixed soil; as well as a combination of silica sand, soil biochar mixture, and gravel. And the plants used in this study are Cyperus Papyrus and Cyperus Rotundus. The purpose of this study is to determine the influence of planting media and the type of plants that will be used in the CW system. All planting media used showed the ability to reduce TSS, COD, and BOD parameters. Although there is a decrease in parameters only with the media, the average efficiency of parameter reduction with plant use has a greater value with a difference of 20% to 25%. For the comparison of the two types of plants, it can be seen that the yield of Cyperus Rotundus is larger, there is a difference in efficiency ranging from 2.5% to 3% with Cyperus Papyrus plant.